The Congruency Hypothesis Revisited: A Reassessment of the Association between Hormonal Contraception, Sexual Satisfaction, and Relationship Satisfaction - Erlin, Tatu (fi=Turun yliopisto|en=University of Turku|, 2017)
Recent research has found empirical support for the hormonal contraceptive (HC) congruency hypothesis, which predicts that a change in women’s HC consumption will result in lower intra-pair sexual satisfaction due to altering the preferences for partner’s traits, although these studies have left room for speculation of the actual effect of HC congruency. To reassess the congruency hypothesis, a large sample of 948 Finnish women was gathered (Mage = 23.95 years, SD = 4.16) who completed an online survey, including items about their current and previous HC use, general relationship satisfaction, and sexual satisfaction. The present study attempted to replicate results from two recent studies that have found support for the congruency hypothesis. A direct replication of one study was performed, and in addition data regarding sexual satisfaction and relationship satisfaction was collected using measures that have been previously validated (Perceived Relationship Quality Components and Female Sexual Function Index). The present study had 98.7% power to detect an effect for the association between sexual satisfaction and HC congruency of the same size as reported in previous studies. However, no support was found for the congruency hypothesis in the present study despite excellent statistical power, and regardless of whether the same measures as used in previous studies of HC congruency or validated measures of sexual satisfaction and general relationship satisfaction were used. Instead, the present study found that the largest mean differences in terms of sexual satisfaction were between the two different congruent HC user groups (i.e., between women who had used HCs both when they first met their partner and at the time of study participation, and women who had not used HCs at either time point), contradicting the congruency hypothesis. These results cast serious doubt on the congruency hypothesis, but the findings suggest a pharmacological main effect of HC use on relationship-related outcomes.